Personalized face emotion classification using optimized data of three features - Muthukaruppan, Karthigayan; Ramachandran, Nagarajan; Mohd Rizon, Mohamed Juhari; Sazali, Yaacob (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org